Impacts of aerobic self-training program on the physical development and preparation of female students - Ragchaa, Gantulga (Proceedings of the Mongolian Academy of Sciences, 2021)
An aerobic self-training program that includes a variety of aerobic activities is important for the development of students' physical and mental fitness, relieving physical and mental fatigue, and preventing physical inactivity accordingly. Aerobics is one of the most self-paced exercises designed to increase heart rate and breathing, as well as body temperature, including large groups of muscles. With a purpose to improve physical development, fitness, preparation level, endurance and metabolism of overweight female students, this study tested an active, high-intensity aerobic exercise program. The weights of students were reduced together with muscle circumference, the general physical development and preparation level were improved accordingly. The results were compared and analyzed to highlight the effectiveness of the training. The results of the study showed a significant improvement in the participants' body weight, body circumference, and body mass index compared to pre-test, intermediate and final results. It shows the importance of the aerobic program.